2021
DOI: 10.3390/molecules26226765
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Parameters of Common Duckweed Lemna minor after the Exposure to Tetracycline and the Recovery from This Stress

Abstract: In this study, the ability of Lemna minor L. to recover to normal growth, after being degraded in a tetracycline-containing medium, was extensively investigated. The plants were exposed to tetracycline (TC) at concentrations of 1, 2.5, and 10 mM. Subsequently, their physiological status was analysed against the following criteria: rate of plant growth; free radical accumulation; antioxidant enzyme activity; chlorophyll content; HSP70 protein content; cell membrane permeability, and mitochondrial activity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 117 publications
2
6
0
Order By: Relevance
“…However, by the end of the experiment, the setups with a higher concentration of streptomycin clearly showed that the fronds had died, suggesting that the antibiotic had a toxic effect on duckweed at a high concentration. This could be explained by the extremely high percentage (93%) of dead mitochondria in duckweed caused by antibiotics in the findings of (Krupka et al, 2021). Maldonado et al (2022) further revealed that the metabolization of antibiotics occurs in three phases in duckweed which contribute to the removal of antibiotics residues in water.…”
Section: Discussionmentioning
confidence: 95%
“…However, by the end of the experiment, the setups with a higher concentration of streptomycin clearly showed that the fronds had died, suggesting that the antibiotic had a toxic effect on duckweed at a high concentration. This could be explained by the extremely high percentage (93%) of dead mitochondria in duckweed caused by antibiotics in the findings of (Krupka et al, 2021). Maldonado et al (2022) further revealed that the metabolization of antibiotics occurs in three phases in duckweed which contribute to the removal of antibiotics residues in water.…”
Section: Discussionmentioning
confidence: 95%
“…A decrease in the content of chlorophyll in plants exposed to anthropogenic environmental factors has been repeatedly observed. The reduction in chlorophyll content in plants treated with antibiotics was demonstrated by Rydzy ński et al [31], Margas et al [89] as well as Krupka et al [38]. However, in most studies assessing the impact of anthropogenic stress factors on chlorophyll, high concentrations of toxic compounds are used.…”
Section: Analysis Of Morphological and Biochemical Parameters Of Comm...mentioning
confidence: 99%
“…The absorbance at λ = 450 nm was measured. In order to compensate for the readings for the natural color of the plant extract, the absorbance was measured at λ = 620 nm, according to Krupka et al [38]. Mitochondrial damage was assessed as a reference (100% viable mitochondria) using the absorbance value of the control sample.…”
Section: Assessment Of Mitochondrial Damage-wst-1 Testmentioning
confidence: 99%
See 2 more Smart Citations